2014
DOI: 10.1007/s00595-013-0808-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary breast peripheral T-cell lymphoma not otherwise specified: report of a case

Abstract: Malignant lymphomas of the breast are rare and primary breast lymphoma comprises <0.5 % of breast malignancies, within which T-cell lymphomas are an even rarer subset. We report a case of primary breast peripheral T-cell lymphoma not otherwise specified (PTCL-NOS). Histology of the biopsied specimen revealed CD2(+), CD3(+), CD4(+), CD5(−), CD7(+), CD8(−), CD20(−), CD25(−), CD30(+), CD56(−), bcl-2(−), EBV-ISH(−), TIA-I(−), and ATLA negative. The patient was treated with six cycles of the CHOP regimen and died 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…Presentation of primary PTCL‐NOS is usually nodal but can also arise from extranodal sites. Primary breast PTCL‐NOS has been reported by Muroya et al . Yoshida et al reported a case of primary PTCL‐NOS involving the thyroid gland.…”
Section: Discussionmentioning
confidence: 97%
“…Presentation of primary PTCL‐NOS is usually nodal but can also arise from extranodal sites. Primary breast PTCL‐NOS has been reported by Muroya et al . Yoshida et al reported a case of primary PTCL‐NOS involving the thyroid gland.…”
Section: Discussionmentioning
confidence: 97%
“…Esto guarda relación con la paciente de nuestro caso, la cual fue diagnosticada al finalizar su embarazo, refiriendo la paciente que las masas en ambas mamas no estaban presentes antes de su embarazo. A pesar de que el LPM ocurre predominantemente en el sexo femenino, se han reportado casos en hombres entre los 60 y 65 años principalmente 13 . Algunos estudios reportan la aparición de los casos a edad temprana, en nuestro caso la edad de presentación fue a los 20 años; esta presentación temprana se asocia a una forma más agresiva, sin embargo no fue así con nuestra paciente, ya que hubo respuesta clínica completa al tratamiento.…”
Section: Discussionunclassified
“…PBL almost occurs in females; however, a few cases were reported in men. The most present age is between 60 and 65 years [ 13 ]. In our study, we found 3 men among 13 patients and the average age was 52.6 years (17–89 years).…”
Section: Discussionmentioning
confidence: 99%
“…Other cutaneous signs like nipple discharge, skin retraction, and local inflammatory signs are rarely seen. Ipsilateral axillary lymph nodes are reported in 13–50% of cases [ 13 ].…”
Section: Discussionmentioning
confidence: 99%